Urban Transformations in Oases: the Case of Mezk ita Oasis, Morocco - Mohamed, Ait Hammou (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to highlight the transformations in housing patterns in the Mazkita oasis, emphasizing some of the spatial imbalances of this type of housing. It also seeks to elucidate one of the pillars of the oasis’s authentic architectural heritage. Additionally, the study reveals numerous urban transformations in their various manifestations amidst the dynamics experienced by the oasis area. Method: This topic was addressed using scientific approach involving geographical and historical methodologies, including observation, analysis, inference, and bibliographic and fieldwork. This included consulting reports and conducting interviews with residents and stakeholders to understand housing transformations in the Mazkita oasis. Results: The urban transformations witnessed by the urban fabric of the Mazkita oasis resulted from the interplay of several causes. The most significant of these include the failure to implement the guidelines of planning and urban development tools, despite the oasis having benefited from several such tools. However, the guidelines of the land use plans specific to the oasis proposed by the master plan for planning and urban development were either not respected, were modified, or remained merely on paper. Conclusion: In general, the southern Moroccan oases have historically experienced human settlement, leaving behind an architectural and cultural heritage evidenced by kasbahs, palaces, and old buildings. However, recent times have seen significant urban transformations affecting various ancient elements, with modern housing replacing traditional structures. This has led to significant spatial imbalances, resulting in the disappearance of the unique characteristics of the oasis area.